2022
DOI: 10.1039/d2dt02597c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into borrowing-hydrogenN-alkylation catalyzed by an MLC catalyst with dual proton-responsive sites

Abstract: Metal-ligand cooperation (MLC) catalysis is one of the most important concepts in the field of organometallic catalysis. However, the diverse functional ligands result in ambiguous mechanisms and constrain the understanding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…This overall mechanistic picture is in line with previous DFT studies reported on hydrogen borrowing processes for the N-alkylation of amines by alcohols catalysed by manganese, 36 cobalt, 37 nickel, 38 ruthenium, [39][40][41] and iridium. 42,43 Figure 3 A) Stochiometric reactivity between activated complex (2) with ethanolamine; B) simplified catalytic mechanism of (de)hydrogenation; C) Energies (G423.15K) of alcohol dehydrogenation for monomer, dimer and trimer (PBE0-D3(BJ)PCM(THF)/def2-TZVP//RI-BP86PCM(THF)/def2-SVP).…”
Section: Mechanistic Investigationssupporting
confidence: 91%
“…This overall mechanistic picture is in line with previous DFT studies reported on hydrogen borrowing processes for the N-alkylation of amines by alcohols catalysed by manganese, 36 cobalt, 37 nickel, 38 ruthenium, [39][40][41] and iridium. 42,43 Figure 3 A) Stochiometric reactivity between activated complex (2) with ethanolamine; B) simplified catalytic mechanism of (de)hydrogenation; C) Energies (G423.15K) of alcohol dehydrogenation for monomer, dimer and trimer (PBE0-D3(BJ)PCM(THF)/def2-TZVP//RI-BP86PCM(THF)/def2-SVP).…”
Section: Mechanistic Investigationssupporting
confidence: 91%